Real-World Evidence Evaluation on the Lipid Profile, Therapeutic Goals, and Safety of the Fixed-Dose Combination of Rosuvastatin/Ezetimibe (Trezete®) in Dyslipidemia Patients - Joel Rodríguez-Saldaña; Francisco Padilla-Padilla; Ernesto G. Cardona-Muñoz; Yulia Romero-Antonio; María Marcela Arguedas-Núñez; José G. Sander-Padilla; Alberto Martínez-Muñoz; Laura A. Lugo-Sánchez; Ileana C. Rodríguez-Vazquez; Jorge González-Canudas (Cardiology Research and Practice)
Introduction. Cardiovascular diseases are the leading cause of death worldwide. The combination of statins and cholesterol-absorption inhibitors promotes the decrease in risk factors, such as high concentrations of LDL (low-density lipoproteins). The aim of the study was to evaluate changes in the lipid profile and the effect on therapeutic goals, as well as the safety of dyslipidemia patients treated with Rosuvastatin/Ezetimibe (Trezete®). Materials and Methods. A real-world evidence study was conducted with retrospective data collection through a review of clinical records from dyslipidemia patients treated with Trezete® in routine medical practice. Clinical records included results of biochemical markers before treatment and at least one follow up between weeks 8 and 16. Results. The study included 103 patients’ clinical records (55.4% men) with a mean age of 56.0 ± 13.0 years. More than 57% of the patients had mixed dyslipidemia and a median disease progression of 3.1 (IQR, 1.5; 9.1) years. Regarding LDL concentrations, 72.8% of the patients achieved therapeutic goals according to cardiovascular risk (CVR), which was statistically significant. Similarly, 94.1% achieved goals for total cholesterol (<200 mg/dL) and 56.0% for triglycerides (<150 mg/dL), a p value <0.001. No cardiovascular events were observed. Conclusion. Trezete® shows an important clinical impact on CVR-related target markers during the treatment of dyslipidemia patients. It is relevant to mention that a significant percentage of patients achieved therapeutic goals during the first months of treatment. Fixed-dose combination therapy has shown to be as safe as monotherapy treatment. ClinicalTrials.gov Identifier: NCT04862962.